Construction of Banjar Women Beauty in Kalimantan Selatan Indonesia - Tutung Nurdiyana (Budapest International Research and Critics University, 2018)
This paper describes the construction of female beauty in the Banjar community. Excavation of data is directed at information about beauty that is owned by the Banjar community. In addition, this paper also explains the shifts that have taken place around Banjar women's beauty treatments. The method used is qualitative ethnography. Beauty in Banjar women is a set of 'knowledge' possessed by Banjar women about beauty that they obtained from generation to generation and is a cultural heritage of the Banjar people. They have local knowledge in beauty treatments or Spa Banjar which is famous as 'timung'. The shift that occurs in Banjar female beauty treatments is a beauty institution, materials used in beauty care, and the concept of beauty.